Employability skills: what do employers need? - Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Balakrishnan Parasuraman; Ena Bhattacharyya; K. S. Savita; Pasupuleti Visweswara Rao; Jayaraj Vijaya Kumaran; Nik Muhammad Sabri Nik Hassan; Rahimah Aris (2021)
This paper will be discussed critically according on the need of employers on graduates employability skills. The emerging of new digital technologies tremendously leads a new way to doing a job. To cope with a need of client almost all jobs in all sectors looking for a new skills to retrain and reskilling their employees. Employers also seeking a fresh graduates whose are meets with their requirement. In current issues, almost all higher education providers doing a research and still explored a particular skills are need to provide to their students, which is meets with employers need. This paper will explain specifically about what are employers needed on graduate employability skills. This is preliminary research to looking a specific skill are very crucial and needed by the employers currently. Sixteen related to employers’ perception toward trait of employability skills in digital era being analysis. According to this analysis, have four main skills are need by an employers, there are basic academic skills, high order thinking skills, technical skills and, employability skills. Through literature review analysis from this study, it’s found 29 attributes must be concentrates to gains employability skills among graduates at higher education institutions. Communication skills is a first priority are concern by employers when they looking at new workers. The second employability skill preferred by employers is problem solving skills and the third priority is critical thinking skills. By validating the construct of employability skills, this study is aimed at providing a general guide to researchers and scholars who would like to embark on similar employability skills studies. The findings also aim provides the holistic view of current trend of global employability skills needed by the graduates which match with the requirement of the industries. Thus, it will minimize the gap between employability skills offered by graduates and the required skills expected by employers in industry.